1999
DOI: 10.1177/0893318999131001
|View full text |Cite
|
Sign up to set email alerts
|

The Discourses of Corporate Spiritualism and Evangelical Capitalism

Abstract: “Should your company save your soul?” asks Fortune magazine in 1991. This article explores the growth of literature proposing corporate spirituality as a means of motivating employees. Critical analysis of this literature suggests that it articulates and advocates two entrepreneurial views of subjecthood (i.e., personal identity) that obscure contemporary corporate power by centering the individual as an autonomous agent, fully responsible for shaping his or her destiny. They either strip individuals of all so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 24 publications
1
89
1
Order By: Relevance
“…However, like organizational storytelling, the introduction of spirituality in the workplace has been criticized by some as being yet another method of behavioral control (e.g., Bell and Taylor, 2003;Nadesan, 1999;Pava, 2003). Others have recently critiqued an instrumental approach in the spirituality at work movement (e.g., Zhuravleva and Jones, 2006).…”
Section: Spirituality In the Workplacementioning
confidence: 97%
“…However, like organizational storytelling, the introduction of spirituality in the workplace has been criticized by some as being yet another method of behavioral control (e.g., Bell and Taylor, 2003;Nadesan, 1999;Pava, 2003). Others have recently critiqued an instrumental approach in the spirituality at work movement (e.g., Zhuravleva and Jones, 2006).…”
Section: Spirituality In the Workplacementioning
confidence: 97%
“…Some have argued that corporate spiritualism runs the risk of overstepping into a coercive relationship with employees (Nadesan 1999;Tourish and Pennington 2002;Goodier and Eisenberg 2006). In the United States, the discussion is further complicated by the very real risk, particularly in public workplaces, that the promotion of workplace spirituality might run afoul of an individual employee's constitutional right to the free exercise of religion (Rhodes 2003;White 2003).…”
Section: Potential Dangers In Examining Spiritualitymentioning
confidence: 98%
“…As to cultural issues, although eastern and western cultures both emphasized the importance of spirituality (Nadesan, 1999), they suggested that spirituality could be cultivated. Thus, for the West, the organizations could construct the employees' workplace spirituality by different systems, whereas the East suggested self-training.…”
Section: General Literature Reviewmentioning
confidence: 99%